(untitled) (Research, Society and Development, 2021)
This study aimed to review the efficacy of methods and use of synthetic or phytotherapeutic products for fungal and microbial control, for materials based on acrylic resin and their impact on the longevity of the dental prosthesis. A bibliographic survey was carried out in PubMed and SciELO databases, using and crossing of Keywords, with restriction filters to the period of publication and language. After removing duplicate articles, the selection of studies was carried out in two stages: reading the title, followed by reading the abstracts. The studies that were selected went through a complete reading and their relevant data were inserted in two standardized tables for data analysis and discussion. 501 articles were select, only 33 of them presented all inclusion criteria, 27 which were laboratory studies, 4 clinical trials, and 2 clinical-laboratory studies. The use of methods for chemical or alternative disinfection, such as heating in microwave energy and immersion in sodium hypochlorite, promote adequate disinfection, but there are significant changes in acrylic resin. Therefore, microbial control strategies using herbal medicines and nanomaterials for inclusion in acrylic resin have been widely studied. Chemical disinfection of dentures is an essential practice for microbial control, and several materials are available for this purpose.